2015
DOI: 10.1371/journal.pone.0146247
|View full text |Cite
|
Sign up to set email alerts
|

Fall Risk Assessment Tools for Elderly Living in the Community: Can We Do Better?

Abstract: BackgroundFalls are a common, serious threat to the health and self-confidence of the elderly. Assessment of fall risk is an important aspect of effective fall prevention programs.Objectives and methodsIn order to test whether it is possible to outperform current prognostic tools for falls, we analyzed 1010 variables pertaining to mobility collected from 976 elderly subjects (InCHIANTI study). We trained and validated a data-driven model that issues probabilistic predictions about future falls. We benchmarked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 43 publications
6
60
1
1
Order By: Relevance
“…The performances of the developed model are comparable with different fall risk assessment tools developed in general community-dwelling population proposed in literature[11, 1518], mainly based on demographic information, self-reported problems with balance and coordination, as shown in Table 3. However, these models have been developed for clinicians caring for the general elderly population and not for ophthalmologists visiting visually impaired people.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The performances of the developed model are comparable with different fall risk assessment tools developed in general community-dwelling population proposed in literature[11, 1518], mainly based on demographic information, self-reported problems with balance and coordination, as shown in Table 3. However, these models have been developed for clinicians caring for the general elderly population and not for ophthalmologists visiting visually impaired people.…”
Section: Discussionsupporting
confidence: 56%
“…Despite the evidences about the importance of visual assessment in patients who have fallen, and the strong attention for falls by the NHS in UK, a Royal College of Physicians audit in 2009 showed that most sites in UK did not employ a standardized visual acuity assessment. Moreover, most models developed to assess fall risk[1118] are typically relying on performance-based physical assessment tasks, which are not usually performed in ophthalmologic clinics [17]. To the best of authors' knowledge, there is no specific tool designed to help ophthalmologists to screen visually impaired subjects for falling risk, during routine ophthalmologic visits.…”
Section: Introductionmentioning
confidence: 99%
“…Model accuracy was achieved by encoding a large number of predictive features, where we perform a series of data aggregation steps, going from tens of thousands of codes (NDC & ICD-9) to hundreds of groupings to the 62 predictive features. The model’s AUC of 0.71 for the validation dataset compares favorably to performance achieved by published models for falls 22 and other conditions. 17, 29 …”
Section: Discussionmentioning
confidence: 60%
“…1319 Models for risk of future falls have been developed for residents of nursing homes, 20 inpatients, 21 and members of a cohort study on aging and mobility, 22 but not yet for the general elderly population. We sought to develop a predictive model that could run universally for those aged 65 years and older based solely on insurance claims.…”
Section: Introductionmentioning
confidence: 99%
“…At the workshop, pharmacists received a range of resources (H. Kale & M. Wilding, unpublished data) including an evidence‐based “quick falls risk assessment tool” (QFRAT) developed by the CCHPS . It includes three “yes/no” questions to assess whether clients:…”
Section: Methodsmentioning
confidence: 99%